ORIENTATION OF STAKEHOLDERS ON THE ECOREGIONAL IDENTITY OF THE GAYO HIGHLANDS FOR ECOTOURISM DEVELOPMENT IN ACEH TENGAH DISTRICT, ACEH PROVINCE - Aswita; Ricky Avenzora; Dudung Darusman; Cecep Kusmana (Indonesian Journal of Forestry Research, 2026)
The massive increase in efforts to develop ecotourism in Indonesia has made the concept of ecoregional identity necessary for strengthening the comparative advantage of inter-regional ecotourism development. This research was conducted to analyze, map, and interpret stakeholder orientation toward ecoregional identity for ecotourism development in the Gayo Highlands, Aceh Province, especially Aceh Tengah District. The study was conducted by analyzing the perceptions, motivations, and preferences of stakeholder groups; by adopting the One Score One Criteria Scoring System for 7 aspects: ecological, socio-cultural, socio-economic, social politics, development, regional, and ecotourism. The analysis showed that stakeholder orientations toward ecoregional identity for ecotourism development remained relatively low: of the 327 ecoregional identity types mapped, only 41% were recognized by stakeholders. The ecoregional identities that are trending and have significant economic value at this time are Gayo Coffee, Lut Tawar Lake, and Depik Fish, which have the highest stakeholder orientation in Aceh Tengah District. This fact not only weakens the functions of other ecoregional identities, which are also important for ecotourism development, but also causes the loss and even extinction of these identities.